Duration Of The Usage Of Dmpa Injects With Amenorrhea In Alita Medika Balong Bendo Polyclinic Sidoarjo 2023 - Endang Sudjatmiastuti,; Ridha Rachmathiany,; Vidia Atika Manggiasih,; I’im Murtiawani, (Journal of Health Science Community, 2023)
Depo MedroxyProgesterone Acetate (DMPA) which gives 150 mg of progesterone in the form of small particles given every 12 weeks by intramuscular injection (in the buttocks area). However, injectable birth control also has many side effects such as weight gain, amenorrhea, headaches, spotting bleeding (Hanafi, 2013). From the results of an initial survey at the Alita Medika Balongbendo Sidoarjo Polyclinic obtained data from 10 respondents showing that there are still many DMPA injection acceptor acceptors with a usage time of more than 2 years that succeeded in amenorrhoea. The purpose of this study was to Analyze the Length of the use of DMPA Injections with Amenorrhea in the Alita Medika Balong Bendo Sidoarjo Polyclinic in 2023. The design of this study was a cross sectional analytic study using a survey (survey research). The population in this study were all DMPA injection KB acceptors who arrived at the Alita Medica Polyclinic Balong Bendo Sidoarjo and took their samples using a nonprobability sampling technique by accidental sampling taken by 25 respondents. The independent variable of this study is the length of the use of DMPA injection KB with a nominal data scale and the dependent variable of this study is the incidence of amenorrhea with a nominal data scale. This research was conducted in January to July 2023 at the Alita Medika Clinic Balong Bendo Sidoarjo. In collecting data from respondents, the next step taken by researchers is to process data by editing, coding, scoring, tabulating, data entry, and cleaning. Data analysis in this study used the coefficient contingency test. From the coefficient contingency test results obtained that the value of p <α = 0.002 <0.005 which means that H1 is accepted is the long relationship between the use of DMPA injection KB with amenorrhea. By using DMPA injection contraception for a long time, amenorrhea will increase. By using DMPA injections for a long period of time, the endometrial growth will be smaller and there will be endometrial atrophy.